Development of a Virtual Reality-Based Environment for Telerehabilitation - Florin Covaciu; Calin Vaida; Bogdan Gherman; Adrian Pisla; Paul Tucan; Doina Pisla (Applied Sciences)
The paper presents an innovative virtual reality (VR)-based environment for personalized telerehabilitation programs. This environment integrates a parallel robotic structure designed for the lower limb rehabilitation of patients with neuromotor disabilities and a virtual patient. The robotic structure is controlled via a user interface (UI) that communicates with the VR environment via the TCP/IP protocol. The robotic structure can also be operated using two controllers that communicate with a VR headset via the Bluetooth protocol. Through these two controllers, the therapist demonstrates to the patient various exercises that the robotic system can perform. With the right-hand controller, the therapist guides exercises for the hip and knee, while the left-hand controller manages ankle exercises. The therapist remotely designs a rehabilitation plan for patients at home, defining exercises, interacting with the rehabilitation robot in real-time via the VR headset and the two controllers, and initiating therapy sessions. The user interface allows monitoring of patient progress through video feedback, electromyography (EMG) sensors, and session recording.